Towards the Model of Learning Management System for Elementary and Secondary Education - Ferry Doringin,; Nisa Zakiati Umami,; Karla Sasia,; Theodorus Pangalila, (Technium Social Sciences Journal, 2023)
This study aims to evaluate teachers' perceptions of the platform X as the Learning Management System (LMS) that is used during and after the Covid-19 pandemic. The Platform X is claimed as a better platform than other LMS because it becomes a solution for many schools in terms of easy implementation, integration, and response to the needs of the students as digital natives. Using the Technology Acceptance Model (TAM), the research evaluates the perception of the 110 teachers in some provinces in Indonesia regarding the usefulness (perceived usefulness), and the ease of use of the LMS. The researchers use the quantitative and qualitative (mixed) method in the design of the research. The researchers surveyed the self-efficacy (the mastery of the LMS) and the features of the LMS to see the teachers’ perceived usefulness. The researchers also surveyed the quality of the system and the quality of the service to evaluate the ease of use of the LMS. The interview with the 4 respondents is conducted to clarify and complete some responses in the survey. The result of the study said that the teachers have a good perception regarding the usefulness and ease of use of the LMS. The result stresses the easy implementation of the LMS, the integration of the application, and the ability of the LMS to respond to the needs of the students as digital natives.